Kualitas Pelayanan Kependudukan Berbasis Digital Melalui Identitas Kependudukan Digital Pada Dinas Kependudukan Dan Catatan Sipil Kota Kendari - Wa Ode Srijuna Ramayana; Wa Limuna (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2026)
Service is one of the functions of government which is the government's obligation in the series of state administration. In the process, there are efforts to transform service activities towards the digital era, which aims to ensure that community needs are no longer limited by space and time, while also responding to very dynamic social changes. Digital Population Identity is a form of responsiveness to social change as referred to in population services. However, in reality, various problems are still found in the field regarding its implementation. This research uses service indicators according to Zethaml with a descriptive qualitative research method. The results show that the quality of digital-based population services is still not optimal due to inadequate internet networks both in institutions that provide population services and in all city administrative areas, limited budgets in supporting the digitalization of services, minimal dissemination of information which then affects the digital literacy of the community and the discriminatory attitudes of certain employees in providing services. To overcome this, an adequate budget is needed to support digitalization efforts, disseminate information to increase public literacy, and implement strict sanctions for employees who violate procedures. Key Words : Service Quality, Digital Services, Digital Population Identity